Analytics： The Real-World Use of Big Data in Financial Services Studying with Judge System Events - 陈思恩 杨律青 徐守辉 (Shanghai jiao tong da xue xue bao, 2016)
＂Big data＂ which admittedly means many things to many people is no longer confined to the realm of technology. Today it is a business imperative and is providing solutions to long-standing business challenges for banking and financial markets companies around the world. Financial services firms are leveraging big data to transform their processes, their organizations and the entire industry. Since 2012, the term ＂big data＂ has frequently been mentioned and used to describe and define the huge amount of data in the information explosive era and to name related technological development and innovation. As to the police work, the coming of big data era is not only a challenge but also an opportunity. Police agencies should go with the tide of development to start with such aspects as work thinking, top design, public information sharing and application and talent provision so as to promote the new development and progress of police work. This paper expounds the practical effect and significance of police big data application by cases happened in some areas.